Impact of the Credit Rating Agencies on the Financial Crisis 2007–2009 - Marciniak, Piotr (Annales. Etyka w Życiu Gospodarczym, 2015)
The paper presents some ethical aspects of the credit rating agencies (CRAs) marketin the light of the latest economic crisis of 2008. A historical background is alsoshown and how the CRA market emerged. It is emphasised how the functioning ofCRAs contributed to the outbreak of the crisis and what were the consequences ofover- or underestimated rating grades. The downgrading of a country has a significant influence on the deterioration of the economic condition. Simultaneously, itafflicts the citizens, who have to pay for it e.g. with higher tax rates. It is believedthat overestimated ratings lead to a speculative bubble, which ends up with the crisis. The paper indicates the problems connected with the way that CRAs operateand how they relate to business ethics. The fact that those institutions are profitprofile entities, which earn their income from clients, whose financial instrumentsare assessed, may bring about a conflict of interests. Moreover, it is outlined howthe governmental policies of countries left CRAs without any particular control,which in the end was a significant factor, too. Finally, some potential solutions arediscussed, and how the approach of CRA managers should change in order to prevent the market from similar situations in the future.